2020
DOI: 10.1002/ana.25958
|View full text |Cite
|
Sign up to set email alerts
|

Network Fingerprint of Stimulation‐Induced Speech Impairment in Essential Tremor

Abstract: Objective This study was undertaken to gain insights into structural networks associated with stimulation‐induced dysarthria (SID) and to predict stimulation‐induced worsening of intelligibility in essential tremor patients with bilateral thalamic deep brain stimulation (DBS). Methods Monopolar reviews were conducted in 14 essential tremor patients. Testing included determination of SID thresholds, intelligibility ratings, and a fast syllable repetition task. Volumes of tissue activated (VTAs) were calculated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Considering that stimulation amplitude is also often increased in patients, who are affected more severely or respond poorly to DBS ("non-responder"), this could lead to an over-representation of non-responding patients in the tractography analysis. Such an adjustment is in line with other DBS mapping studies that controlled for the amplitude [33][34][35] .…”
Section: Connectivity Analysissupporting
confidence: 82%
“…Considering that stimulation amplitude is also often increased in patients, who are affected more severely or respond poorly to DBS ("non-responder"), this could lead to an over-representation of non-responding patients in the tractography analysis. Such an adjustment is in line with other DBS mapping studies that controlled for the amplitude [33][34][35] .…”
Section: Connectivity Analysissupporting
confidence: 82%
“…Here, several groups have tried using VTA models to solve this task. For example, similar to Tsuboi’s characterization of stimulation induced dyskinesia in PD, Petry-Schmelzer et al sought to determine the brain network fingerprint of stimulation induced dysarthria in ET patients as well as build a predictive model for stimulation related speech intelligibility after thalamic DBS ( Petry-Schmelzer et al, 2021 ). FEM-based VTAs were used to evaluate structural connectivity using a discriminative fiber tract analysis within a normative connectome.…”
Section: State-of-the-art In Clinical Studiesmentioning
confidence: 99%
“…This medial activation profile aligns with the face-related cellular somatotopy of internal VIM [ 71 ] as well as a study by Matsumoto and colleagues showing that stimulation-induced dysarthria occurred with more medial thalamic stimulation [ 77 ]. Other studies have also suggested that stimulation overlapping the CTT was a possible cause of dysarthric worsening of intelligibility [ 27 , 28 ]. Our findings are consistent with these past studies and further suggest that the anterior VIMi afferents of the CTT are specifically those responsible for stimulation-induced dysarthria.…”
Section: Discussionmentioning
confidence: 99%
“…Recent connectomic and tractography studies have focused on the cerebellothalamic tract (CTT) as an effective target for therapy [ 8 , 22 - 26 ]. However, other studies suggest that CTT may also be responsible for stimulation-induced side effects [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%